Research on the influence of casting powders on the higher quality of continuous cast semi-finished parts. Issue 1 (February 2021) - Radu, M; Heput, T; Ardelean, E; Dascal, A
Abstract: Pursuant of the modernization of steel elaboration and casting technologies, at present over 90% of the liquid steel undergoes continuous casting. The quality of the cast parts is influenced by: the casting temperature and rate, the flow rate of the cooling water and the characteristics of the casting powders. The research under consideration was done on a low manganese alloy steel X60QS elaborated in an EBT-type, 100 ton oven and cast on a 5-strand MCT casting machine. The paper gives the results of the research on the variation of the carbon, manganese and sulphur content per cast product for each casting strand and for each rod of the strand. The research managed to establish the causes that lead to deviations from the required chemical content for these elements, as well as the possibilities of eradicating them. The results are applicable in research and in practice.